2017
DOI: 10.1002/jum.14416
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Among Ultrasound‐Guided Diffuse Optical Tomography, Microvessel Density, and Breast Cancer Prognosis

Abstract: The total Hb concentration can reflect a tumor's blood supply. Patients with a high total Hb concentration and microvessel density have a higher risk for a poorer prognosis. Total Hb can be used as an indicator of breast cancer prognosis. Diffuse optical tomography can help physicians identify patients with a high risk of metastasis and make clinical decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…A great body of evidence supports a positive correlation between microvascular density, tumor grade, and aggressiveness [1,2,3]. Indeed, in breast carcinoma and other neoplasias, the incidence of metastatic disease increases with the number of microvessels in the tumor mass [4], highlighting the importance to develop therapeutic strategies targeting angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…A great body of evidence supports a positive correlation between microvascular density, tumor grade, and aggressiveness [1,2,3]. Indeed, in breast carcinoma and other neoplasias, the incidence of metastatic disease increases with the number of microvessels in the tumor mass [4], highlighting the importance to develop therapeutic strategies targeting angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The work [95] was devoted to the study of the possible interconnection between the data acquired with the help of US-controlled DOS and the concentration level of hypoxia-induced factor (HIF-1α) and CD34 in confirmed breast cancer. Immunohistochemical examination of HIF-1α and CD34 revealed differences in the total hemoglobin concentration and microvessel density between the HIF-1α positive and negative groups.…”
Section: Diffuse Optical Spectroscopymentioning
confidence: 99%
“…Niu S et al [25] reported that microvessel density of breast cancer and total hemoglobin (HBT) were linearly correlated. The total Hb concentration can reflect a tumor's blood supply.…”
Section: Diffuse Optical Tomographmentioning
confidence: 99%